3D FEM analysis of the effect of buried phononic crystal barriers on vibration mitigation. (1st October 2019) - Albino, Carlos; Godinho, Luís; Amado-Mendes, Paulo; Alves-Costa, Pedro; Dias-da-Costa, Daniel; Soares, Delfim
Highlights: Innovative strategies of vibration mitigation are analysed. Phononic crystals can mitigate ground vibrations at specific tuned frequency bands. Infinite physical systems with periodic configuration are efficiently modelled. 3D TD-FEM is used since it requires reduced computational effort. Studied geometries, materials and soil properties lead to different band gaps. Abstract: Vibration induced by vehicles is a significant problem in large cities causing a major impact on human activities, comfort and health. Besides well-known strategies to mitigate vibrations and their effects, innovative methods are being devised using novel physical concepts. Those are already well-developed for the case of acoustic barriers, for example made of periodically arranged elements (known as "sonic" or "phononic" crystals), however the shielding of structures from the effect of vibrations is still in an earlier development stage. In this context, this paper describes several studies on the concept of a periodic buried structure, made of stiff inclusions (e.g. concrete), deployed with a geometrical arrangement that may allow efficient filtering of dominant vibration frequencies. A 3D finite element model is used formulated in time domain to perform a detailed numerical assessment of the effectiveness of the proposed shielding device. Simulations are performed using a time-marching algorithm to allow an efficient calculation procedure. Results are promising, clearly revealing the existence of band gaps of large attenuation, although limitations related to the existence of guided waves travelling along the inclusions are also identified.